Capitães da Areia e Tereza Batista: duas fases e duas faces da violência sexual - Costa, Camila Fernandes da (2023)
Over the years, literature, as well as several other cultural vehicles, has reflected and perpetuated stereotypical profiles of women, reflecting social relations and the precepts of patriarchal society. These portraits often mold women into a model of submission, confinement and silencing that perpetuates the practice of sexual violence. With this in mind, this research proposes to analyze the novels by Jorge Amado, Capitães da Areia (1937) and Tereza Batista Cansada de Guerra (1972), taking as its guiding axis the analysis of the representation of sexual violence present in these literary texts, victimizing, in the first, a secondary character and, in the second, the protagonist. We will therefore investigate the way in which the violence that permeates rape presents itself and reinforces stereotypes or criticizes such values that surround sexual abuse. For this analysis to be possible, support for feminist criticism was essential, especially its focus on the study of the female gender and its representations in literature and the debates surrounding sexual violence and its relationship with patriarchy. Therefore, this work dialogues with the studies developed by Federici (2017), Priore (2015) and Davis (1981) to understand the history of women in Brazil and the world, the latter focusing on black women; by Beauvoir (1949), Millett (1970) and Brandão (2006), which establish the relationship between feminist criticism and literary studies; Brownmiller (1975), Davis (1981), Negreiros (2021) and Araújo (2022), with regard to the analysis of sexual violence. In addition to using as a reference the criticism of Amadiana's work related to gender studies through the analysis of various studies developed: Galvão (1976), Duarte (1996), Rayol (2011). The study aims to observe how the voices present in the narratives combine in order to represent this violence committed against female characters. Based on this observation, the research aims to examine how these resources help in the representation of the different violence that permeates the novels, taking into account that each narrative has its singularities that illustrate the different social, historical and cultural contexts. Therefore, to understand these aspects, literature was observed from a historical perspective and its relationship with gender studies. Through this study, in addition to contributing to literary studies about female representations, there is collaboration in the analysis of the representation of sexual violence in fictional texts. From the analysis of Jorge Amado's narratives, it is possible to affirm that the figurations of sexual violence change in different phases, which are related to the compositional characteristics present at each moment of production and with the values present at each time.